The meaning of mainland Portugal beaches and dunes’ psammophilic plant communities: a contribution to tourism management and nature conservation - Martins, Mónica C. (2017)
Due to their position of interface between the sea and land, the flora and vegetation of coastal beaches and dunes, occupy ecologically extreme, sensitive, unique and valuable habitats. The occurrence of a large number of endemic taxa and specific plant associations endowed with key ecological services and adapted to a stressful and harsh environmental gradient, gives them a high interest for nature conservation and an important role in sustainable territorial planning. However, such ecosystems are vulnerable to the disruption caused by several anthropogenic sources. Among other global threat factors, the inevitable sea rise caused by climate change and, at a local scale, the non-negligible implications of trampling caused by disorderly coastal touristic exploitation, growing construction pressure in the littoral, and a seasonal population boom in late spring and in summer, plus all derivate forms of pollution, are threat factors to their integrity. Therefore, a correct planning of the touristic economic activities requires the understanding of the vegetation composition and spatial distribution patterns, intrinsically determined by their biogeographic context in the Euro-Siberian or Mediterranean Regions. This comprehensive work, based on a broad phytogeographic study, brings together disperse information on plant communities of the Portuguese sandy coasts (beaches and dunes), by analysing floristic compositions, chorology and ecological characteristics, and matching them with the “Nature 2000” network habitats. Resilience and vulnerability are also studied. In a nature conservation perspective, a positive balance (and a sustainable co-existence) between the preservation of natural values and human development in the Portuguese coast, will benefit with the integration of this knowledge in coastal planning and management activities.